2018
DOI: 10.1148/radiol.2018171730
|View full text |Cite
|
Sign up to set email alerts
|

Connection Disruption Underlying Attention Deficit in Subcortical Stroke

Abstract: Purpose To investigate neural substrates underlying attention deficit in patients with chronic subcortical stroke by combining voxel-based lesion-symptom mapping (VLSM) and diffusion-tensor (DT) tractography. Materials and Methods Institutional review board approval and written informed consent were obtained. Diffusion magnetic resonance imaging data were prospectively acquired from August 1, 2014, to March 30, 2015, in 49 patients (32 men, 17 women; mean age, 55.7 years ± 8.0; age range, 40-71 years) with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We further perform a two-sample t -test for lesion volume (ml) between the patients with FMA >10 and those with FMA ≤10, not showing significant difference between these two subgroups (Mean ± Std: 7.85 ± 5.86 ml for FMA ≤10); 9.32 ± 5.38 ml for FMA >10; p = 0.44). We also performed a voxel-based lesion-symptom mapping (VLSM) analysis ( Bates et al, 2003 ; Liu et al, 2018 ). The VLSM results suggested that stroke patients do not show significant correlations (at a voxel-wise threshold of p < 0.001, uncorrected) between lesion location at chronic stage and both FMA scores and entropy values.…”
Section: Resultsmentioning
confidence: 99%
“…We further perform a two-sample t -test for lesion volume (ml) between the patients with FMA >10 and those with FMA ≤10, not showing significant difference between these two subgroups (Mean ± Std: 7.85 ± 5.86 ml for FMA ≤10); 9.32 ± 5.38 ml for FMA >10; p = 0.44). We also performed a voxel-based lesion-symptom mapping (VLSM) analysis ( Bates et al, 2003 ; Liu et al, 2018 ). The VLSM results suggested that stroke patients do not show significant correlations (at a voxel-wise threshold of p < 0.001, uncorrected) between lesion location at chronic stage and both FMA scores and entropy values.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies ( Biesbroek et al, 2017 ; Tu et al, 2017 ; Liu et al, 2019b ) have revealed that SVCI patients exhibit nearly global changes with decreased FA and increased MD in WM tracts especially those located in thalamic-prefrontal and caudate-prefrontal pathways. It has been proven that these two pathways are markedly related to neuropsychological assessments of executive function, attention, and processing speed in many task-related functional studies ( Block et al, 2007 ; Müller-Oehring et al, 2015 ; Liu et al, 2018 ). Our study showed that the TMT-B assessment was significantly different between the patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…LSM successfully identified neural substrates of survival and language outcomes after adult brain tumor78; LSM identified neural substrates of language,79–81 motor,82 word comprehension,83 voice recognition,84 attention,85 computational ability82 and somatosensory outcomes86 after adult stroke lesions, etc. These studies used one LSM model, not three, and mostly V-LSM, the basic LSM model.…”
Section: Methods and Analysismentioning
confidence: 99%